Linear programming in criminal justice administration - Hy, Ronald John (American journal of criminal justice, 1984)
Most criminal justice administrators can no longer rely on a single problem solving technique. Consequently, effective administrators must become familiar with (though no experts in) various techniqes. Linear programming (LP) is a powerful managerial technique which provides narrow-range solutions to problems in which the impact of key variables is both linear and certain. LP is especially useful when applied to problems involving the allocation of limited resources. This article discusses a simple how-to appraoach to LP, which is a mathematical problem solving computation that provides solutions which can be applied under conditions of certainty. Besides defining the key characteristics of LP, this article illustrates the procedures used to calculate the simplex method, the most widely used method for calculating a set of LP equations. The simplex method is mathematically efficient because it considers only the best solutions with a minimum number of solutions computed. Once the solution is computed, it is relatively easy to interpret the computer output.